Fibromyalgia Syndrome among Iraqi Patients with Knee Osteoarthritis. - Al-Rawi, Ziad S.; Gorial, Faiq I.; Ali, Wafi H. (Journal of the Faculty of Medicine Baghdad, 2014)
Back ground: Fibromyalgia syndrome (FMS) is a common chronic musculo-skeletal disorder resulting in chronic widespread pain impacting on quality life.Objectives: To assess the relationship between FMS and knee osteoarthritis (KOA) and to evaluate the predictors of this relationship if present.Patients and Methods: One hundred Iraqi KOA patients and 100 healthy controls were included in this cross-sectional study. Full history was taken and complete clinical examination was done for all patients. Baseline characteristics [age, sex, duration, body mass index (BMI), waist circumference, family history (Hx) of KOA, smoking history, and drug history.] were also documented. Laboratory analysis included complete blood count, erythrocyte sedimentation rate (ESR), thyroid stimulation hormone, serum calcium, serum alkaline phosphatase, serum phosphate, and anti-nuclear antibody were done for all patients. X-rays of both Knees was taken for patients and was graded according Kellgren and Lawrence scale. The American College of Rheumatology (ACR) criteria for classification and reporting osteoarthritis of the knees were applied on both groups. Individuals in both groups were assessed for FMS and the American College of Rheumatology 1990 Criteria for fibromyalgia were applied for both groups. Comparative statistics were done using Chi square test for categorical variables and students' independent 2 samples (t) test for continuous variables.Results: FMS was present in 26 of 100(26%) KOA patients compared to 7(75%) of 100 of controls [odd ratio (OR)=4.6(95% CI(1.92-11.35),p=0.001]. Frequencies of associated features (headache, sleep disturbances, fatigue, depression, anxiety, and parasthesia) were significantly more in patients than that of controls (P